(untitled) (Eurasian Medical Research Periodical, 2024)
In modern obstetrics, the medical and social significance of infections is due to their significant contribution to the formation of maternal morbidity and mortality rates [1–3]. Despite significant advances in diagnosis and antimicrobial therapy, according to the conclusions of WHO experts [4], the share of postpartum sepsis in the structure of maternal mortality in the world is quite high.